2023
DOI: 10.1186/s13722-023-00383-0
|View full text |Cite
|
Sign up to set email alerts
|

Improving alcohol health literacy and reducing alcohol consumption: recommendations for Germany

Abstract: Background Although the detrimental health effects of alcohol are well established, consumption levels are high in many high-income countries such as Germany. Improving alcohol health literacy presents an integrated approach to alcohol prevention and an important complement to alcohol policy. Our aim was to identify and prioritize measures to enhance alcohol health literacy and hence to reduce alcohol consumption, using Germany as an example. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
(70 reference statements)
1
1
0
Order By: Relevance
“…FHL screenings may be considered for implementation by clinicians who see individuals presenting PTSD and hazardous alcohol use. Further, there may be merit to offering greater attention to improving alcohol health literacy as part of prevention (19,29), consistent with earlier recommendations (30).…”
Section: Discussionsupporting
confidence: 63%
“…FHL screenings may be considered for implementation by clinicians who see individuals presenting PTSD and hazardous alcohol use. Further, there may be merit to offering greater attention to improving alcohol health literacy as part of prevention (19,29), consistent with earlier recommendations (30).…”
Section: Discussionsupporting
confidence: 63%
“…We perform ceteris paribus exercises in order to isolate the effects of different control variables, and get a better understanding of the situation. However, Manthey et al (2023) demonstrated that warning information about product use that potentially curve consumption must be complemented with taxes (pricing). Both approaches should be integrated as part of a comprehensive strategy aimed at mitigating the burdens on public health, social well-being, and economy, of marijuana use.…”
Section: Marijuana Legalizationmentioning
confidence: 99%